CONTINENTAL PLATE COLLISION: UNSTABLE VS. STABLE SLAB DYNAMICS - Toussaint G.; Burov E.; Jolivet L. (My University, 2004)
We study possible scenarios for the evolution of continental collision zones by using a dynamic thermomechanical model that includes brittle-elastic-ductile rheology, surface erosion, and explicit metamorphic changes. This paper focuses primarily on the influence of four key parameters: (1) geotherm or thermotectonic age (which controls the rheological profile), (2) lower-crustal composition (weak or strong rheology), (3) convergence rate, and (4) metamorphic changes in the downgoing crust. The experiments suggest that, depending on these parameters, plate convergence is accommodated by four distinct mechanisms: stable subduction, shortening by pure-shear thickening or folding, and Rayleigh-Taylor instabilities. It appears that stable, oceanic-type subduction can only occur in the case of cold lithospheres (Moho temperature, TMoho 4 5 cm/yr). Depending on the lower-crustal rheology (strong or weak), either the whole (upper and lower) crust or only the lower crust can be involved in subduction. It appears that in the case of weak metamorphic rheologies, phase changes only slightly improve chances for stable subduction. Lithospheric shortening becomes a dominant mechanism when TMoho > 550 °C or convergence rates are 650 °C). Large-scale folding is favored in the case of TMoho = 500 650 °C and is more effective in the case of mechanical coupling between crust and mantle (e.g., strong lower crust). Gravitational (Rayleigh-Taylor) instabilities overcome other mechanisms for very high values of TMoho (>800 °C) and may lead to development of subvertical cold spots.